EVALUASI KEMAMPUAN LAHAN DESA SIHITONG, SINAR SABUNGAN DAN LUMBAN LOBU KABUPATEN TOBA SAMOSIR - Sitohang, Julpan Lynneus; Sitorus, Bintang; Sembiring, Mariani (Universitas Sumatera Utara, 2013)
Land capability evaluation is an evaluation of land potential for use of various farmingsystems in general without specifying the allocation to certain crops and management actions. Theresearch was conducted in April of 2012. The purpose of this study was to determine the landcapability class on Sihiong, Sinar Sabungan and Lumban Lobu Village Toba Samosir Distric withthe method of limiting factors and matching according to land capability class Arsyad (1989).Analysis of the soil such as soil texture, permeability, bulk density, salinity and organic material areconducted in the Laboratory of Research and Technology, Faculty of Agriculture, University ofNorth Sumatra and field observations such as slope, erosion factors, soil depth, drainage, gravel /rock and inundation / flood hazard. The results showed that areas Sihiong, Sinar Sabungan andLumban Lobu has actual land capability class is the same class III (es), Class III is in which landcan be used for the production of crops and forests, (es) an limiting factor on erosion and the depthof the root zone or soil (solum). So the capability class of potential land become III (s), which (s) isa limiting factor on the rooting area only.Keywords: evaluation of land capability, survey, BPS Tobasa